OPTIMIZATION OF TOTAL PHENOLIC CONTENT FROM BLACK GRAM EXTRACT USING RESPONSE SURFACE METHODOLOGY - LINY. P,; MANISH KHODWE, (International Journal of Pharma and Bio Sciences, 2017)
Blackgram have the antioxidant properties because of the presence of the natural phenolic compounds which has beneficiary effects. In the present work, polyphenols are extracted using solid liquid extraction in a batch reactor at constant temperature. The polyphenol content is determined using the Folin- Ciocalteau method and expressed as Gallic Acid Equivalents (GAE). The effect of the solvents ethanol, methanol, acetone and water were studied on the parameters pH, extraction temperature and extraction time on Total Phenolic Content have been checked and it was optimized using a three variable, threelevel Box-Behnken response surface methodology for extracting phenolic content. Validation of the model is based on the predicted and the observed values. The quadratic model predicted total phenolic content of 25% and ethanol extracts is 68.6 mg GAE/g of dry black gram powder sample. HPLC analysis showed the presence of phenolic acids and flavonoids.